Living with Risk - EPSTEIN, LARRY G. (Review of Economic Studies, 2008)
Living with risk can lead to anticipatory feelings such as anxiety or hopefulness. Such feelings can affect the choice between lotteries that will be played out in the future—choice may be motivated not only by the (static) risks involved but also by the desire to reduce anxiety or to promote savouring. This paper provides a model of preference in a three-period setting that is axiomatic and includes a role for anticipatory feelings. It is shown that the model of preference can accommodate intuitive patterns of demand for information such as information seeking when a favourable outcome is very likely and information aversion when it is more likely that the outcome will be unfavourable. Behavioural meaning is given to statements such as “individual 1 is anxious” and “2 is more anxious than 1”. Finally, the model is differentiated sharply from the classic model due to Kreps and Porteus.